ИНТЕЛЛЕКТ ТЕСТЛЕРИН БЕЙИМЛЕСТИРИЎ МАШҚАЛАЛАРЫ: ДИАГНОСТИКА БАСҚЫШЛАРЫ ҲӘМ ИНСТРУКЦИЯ - Турдымуратова, А.Б. (FAN va JAMIYAT, 2019)
The article deals with a brief history of intelligence tests the structure of intellect, the stages of adaptation of intellect tests, and methods of standardizing the results of psychological measurements are given.